The galea Magna shipwreck – archaeological evidence and archival sources of a Venetian war galley of 1598 - Zongolo, Fernando; Auriemma, Rita; Podestà, Andrea (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
Since 1999 and until 2021, numerous scattered remains of a presumed Venetian ship (weapons, coins, pottery, etc.) have been recovered from the shallow waters of the ‘trap-bay’ of Torre S. Sabina (Carovigno, Brindisi, Italy). Through extensive archival research and the study of the artifacts recovered, we were able to identify these finds as belonging to the galea Magna. On 11 November 1597, the galea, under the command of Marc’Antonio Magno, a Venetian sopracomito (ancient Venetian term for a noble commander of a galley), set sail from the island of Crete to Venice, following the common shipping route along the eastern Adriatic coast. A storm forced a change of route (Fig. 1) which, combined with the darkness of the night, caused the ship to run aground on the cliffs and sink at the entrance to the bay on 1 January 1598.